Pembuatan Otomatisasi Digital Marketing Instagram Yumaree Coffee - Perawati, Gina Nurlatipah (Ebiz Prima Nusa, 2022)
Digital marketing automation is a service to manage, run, and automate marketing activities to help people work more effectively and efficiently. However, the digital marketing situation at Yumaree Coffee has not gone well, especially on Instagram. This is due to the absence of an automated marketing digitalization system. This project aims to find out what the state of Yumaree Coffee's Instagram is and how to make digital marketing automation on Yumaree Coffee's Instagram. Making this Instagram digital marketing automation includes Auto Like, Auto Comment, Auto Follow, Auto Scheduling, Auto Unfollow, Auto Direct Message, Auto Link, Auto View Story, Auto Hashtag, and Report Insight which can increase interaction with consumers. The creation of this digital marketing automation project is focused on the Yumaree Coffee Instagram application. This automation design utilizes Instagram as its object using the Waterfall method, SWOT analysis on Instagram, and Digital Marketing to find out more deeply what the opportunities and challenges of the project are. From the results of trials and evaluations after direct testing within one week, it was concluded that Yumaree Coffee's Instagram digital marketing automation helped increase interactions to reach broader consumers effectively and efficiently.